2018
DOI: 10.1136/bmjsem-2017-000302
|View full text |Cite
|
Sign up to set email alerts
|

Acetazolamide reduces exercise capacity following a 5-day ascent to 4559 m in a randomised study

Abstract: ObjectiveTo assess whether acetazolamide (Az), used prophylactically for acute mountain sickness (AMS), alters exercise capacity at high altitude.MethodsAz (500 mg daily) or placebo was administered to 20 healthy adults (aged 36±20 years, range 21–77), who were paired for age, sex, AMS susceptibility and weight, in a double-blind, randomised manner. Participants ascended over 5 days to 4559 m, then exercised to exhaustion on a bicycle ergometer, while recording breath-by-breath gas measurements. Comparisons be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 29 publications
3
11
0
Order By: Relevance
“…Reductions in post-exercise α1-AGP by acetazolamide were unrelated to the significant improvements in exercise SpO 2 at similar intensity (these effects of acetazolamide on exercise performance were previously published and support previous findings) 26 39. On its own, this would provide further support indicating that hypoxia is not the primary mechanism of post-exercise proteinuria.…”
Section: Discussionsupporting
confidence: 86%
“…Reductions in post-exercise α1-AGP by acetazolamide were unrelated to the significant improvements in exercise SpO 2 at similar intensity (these effects of acetazolamide on exercise performance were previously published and support previous findings) 26 39. On its own, this would provide further support indicating that hypoxia is not the primary mechanism of post-exercise proteinuria.…”
Section: Discussionsupporting
confidence: 86%
“…Acetazolamide (AZ) is a carbonic-anhydrase (CA) inhibitor commonly used for prevention and/or treatment of symptoms of acute mountain sickness (AMS) during ascent to high altitude (8,25). For recreational climbers and for those who work at altitude, such as the military and emergency medical responders, the use of AZ allows for the completion of tasks or missions that can be made more difficult by AMS symptoms (e.g., fatigue, headache, nausea, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…AZ has been shown to decrease exercise performance at sea level (27,29); however, studies examining the impact of AZ on exercise at altitude have reported conflicting results (8,9,25). Some authors report that AZ decreased performance (8,15), whereas others have reported that AZ has no impact on performance (12,14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some papers the acetazolamide was proven way to prevent or cure mountain sickness even though Bradwell and al. (2018) found in a randomized study that it reduces exercise capacity following a 5-day ascent to 4559 m. Even though the acetalazomid might reduce the symptoms of acute mountain sickness ( Hung et al, 2019, Gonzales et al, 2018 none of the subjects in this study used any drugs of that type in order to prevent or cure mountain sickness.…”
Section: Discussionmentioning
confidence: 99%